Role of CD38 in Airway Function - Kang, Bit N.; Guedes, Alonso G.P.; Tirumurugaan, K. G.; Jude, Joseph A.; Deshpande, Deepak A.; Panettieri, Reynold A.; Amrani, Yassine; Lund, Frances E.; Walseth, Timothy F.; Kannan, Mathur S. (Current Respiratory Medicine Reviews, 2006)
CD38, a 45-kDa cell surface glycoprotein, is involved in the synthesis of the calcium mobilizing second messenger molecule cyclic ADP-ribose. Cyclic ADP-ribose is known to release calcium from the sarcoplasmic reticulum of airway smooth muscle cells. The pharmacological features of cyclic ADP-ribose-mediated calcium release in airway smooth muscle cells are distinct from those mediated by inositol 1,4,5-trisphosphate and involve activation of ryanodine receptor channels. In airway smooth muscle cells, contractile agonists recruit cyclic ADP-ribose for intracellular calcium release in a receptor- and receptor-subtype-specific fashion. The CD38/cyclic ADP-ribose signaling has a role in airway function, since methacholine-induced airway resistance is significantly lower in CD38 deficient mice than in the wild type controls. The diminished airway responsiveness appears to result from lower intracellular calcium responses to spasmogens. In human airway smooth muscle cells, inflammatory and Th-2 cytokines increase the expression of CD38 and augment the capacity for cyclic ADP-ribose-mediated calcium release during agonist stimulation. These results suggest a role for cyclic ADP-ribose in airway smooth muscle hyperresponsiveness during inflammation. This review will focus on the role of CD38 and cyclic ADP-ribose in normal airway function and its potential contribution to airway hyperresponsiveness in inflammatory diseases such as asthma.
Keywords: cytokines